Clinical features, laboratory characteristics and outcome of patients with drug-induced acute liver failure - Nabi, Tauseef; Rafiq, Nadeema; Jamil, Imran; Arifa, Quratul Ain (International Journal of Advances in Medicine, 2019)
Background: Acute liver failure (ALF) is a rare medical emergency. Its rapid progression and high mortality demand early diagnosis and expert management. Drug-induced ALF (DI-ALF) remains the uncommon cause of ALF in India. Clinical and etiological profile varies with geographical area and time. A prospective study of DI-ALF was carried with the aim to determine the clinical features, laboratory characteristics, outcome and hospital course. Methods: A total of 15 patients with a diagnosis of DI-ALF were included in the study. The variables evaluated were demographic, signs and symptoms, biochemical parameters [bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), prothrombin time (PT), internal normalization ratio (INR) etc.], outcome and course during hospitalization. Results: Out of 15 DI-ALF patients, 12 had Anti-tuberculosis therapy (ATT) induced ALF and 3 patients had ayurvedic induced ALF. Majority of the patients were females (73.3%) and middle-aged (42.60±14.30 years). Coma grade at the time of admission showed that majority of patients (66.8%) had grade I and II encephalopathy. Depending on the pattern of liver injury, hepatocellular pattern was most common (53.3%) followed by mixed and cholestatic pattern. 40% of patients died with DI-ALF complications of which ATT induced ALF contributed 41.7%. Mean AST was more increased as compared to ALT. Development of ascites (P = 0.030) and mannitol use (P = 0.025) was significantly more common in non survived group than survived group. Length of hospital stay was significantly more in non survived group than survived group (P = 0.009). Conclusions: ATT was the class of drugs most frequently associated with DI-ALF. DI-ALF disproportionately affected middle-aged women. Most DILI ALF patients had hepatocellular injury pattern. 40% of patients died with DI-ALF complications. Development of ascites, mannitol use and length of hospital stay was significantly more in non survived group than survived group.